VD_FINDINFO HC / 2023 / 618 vom 2. Oktober 2023 - VD Tribunal cantonal (2023)
OBLIGATION D'ENTRETIEN, REVENU, LIBÉRALITÉ, DROIT DE GARDE, VISITE, DOMICILE, CHANGEMENT DE RÉSIDENCE | 134 al. 2 CC, 163 CC, 176 al. 1 ch. 1 CC, 179 al. 1 CC, 273 CC, 276 CC, 285 CC, 318 al. 1 let. c CPC (CH)